Variation in Campylobacter phage and prophage - Liang, Lu (2017)
Campylobacter is a bacterial pathogen commonly responsible for foodborne gastroenteritis worldwide. Due to the rapid development of resistance to antibiotics, many alternative interventions have been studied and bacteriophage therapy is one of them. To maximise the impact of the intervention and to ensure it remains sustainable it important to study the ecology and coevolution of Campylobacter and the bacteriophage that infect the pathogen.